The Effect of Social Media Marketing on Brand Awareness and Brand Image to Increase Intention to Buy (Study on Audia Multibrand Muslimwear) - Audeva Azhar Muhamad; Muhammad Fikry Aransyah (Budapest International Research and Critics University, 2022)
The amount of pressure from external and internal makes entrepreneur always innovates and develop more strategies so that their business can survive and be better in the future. One strategy that can be done is use social media as their marketing media tool, social media makes business's attention, awareness, and image increases. Instagram is one of the best platforms to implement social media marketing with its many features and flexibility in terms of content creating and content sharing, it can increase sales traffic and as an influential media regarding the products being sold. The Audia Multibrand Muslimwear boutique uses Instagram with the username @audiastore, this boutique has recently maximized the use of Instagram from the previous only to display catalogs that are sold in stores, and is now also active and consistent in terms of creating interactive content about the boutique, maintaining good relations with virtual customers, and also make buying and selling transactions through Instagram and with this research, researchers want to find out with all the strategies carried out by Audia Multibrand Muslimwear will affect brand awareness and brand image and also whether it increases the buying interest of Instagram users and customers to Audia Multibrand Muslimwear’s Instagram, @audiastore.